Влияние контактной точечной сварки на структурно-фазовые особенности проволоки на основе никелида титана - Гарин, Александр Сергеевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
Resistance spot welding is widely used in industry for joining wires and other metallic materials. In this study, the effect of resistance spot welding on the structural and phase features of wire based on titanium nickelide was studied. Experiments were carried out using wires of various thicknesses, and the parameters of the structure and phase composition of the wire were measured. As a result of the study, it was found that resistance spot welding can significantly change the structural features of the wire based on titanium nickelide, features in the places of welded joints. However, when using a wire with a diameter of 200 microns in certain welding modes, the microstructure of the welded joints does not actually differ from the microstructure of the wire. These results can be useful for the development and optimization of the production of implants and medical devices based on titanium nickelide.